The Contribution of Women Farming Workers on Household Income : Case Study in Sugihwaras Village, Kalitengah District, Lamongan Regency - Emmy Hamidah; Endang Tri Wahyurini (Kadiri University - Faculty of Agriculture, 2023)
The village of Sugihwaras of Lamongan Regency is an agricultural area where most of the farmers are paddy farmers with female farm workers. One aspect to examine in the area is the role of rural women in agriculture as members of the household, the outpouring of workdays they do for their daily activities, and to what extent this affects their family's farming income. The study aimed to determine the number of working hours and the contribution of female farm labourers to household income. The study employed a simple random sampling of 60 respondents with interview techniques using a questionnaire. The method of analysis was descriptive analysis. The results obtained that the working hours of female farm workers for one year per hectare of the land area were 540 hours, devoted to paddy farming twice annually. The contribution of female farm workers to household income was IDR 1,687,500 per month or IDR48,600,000 per year per hectare, from paddy farming for two growing seasons annually. It is suggested that the amount of working hours and the contribution of female farm workers to household income is very small, so efforts should be made to increase the number of hours they work so that the income they earn can increase. Efforts are being made, namely raising livestock, as well as training in the manufacture of processed by-products of agriculture, for instance by making sweet potato chips and other preparations that can be sold.